2019
DOI: 10.1016/j.fpsl.2019.100424
|View full text |Cite
|
Sign up to set email alerts
|

TPCS/PBAT blown extruded films added with curcumin as a technological approach for active packaging materials

Abstract: The development of active packaging is a relevant topic demanding the development of films with diverse properties to preserve specific foodstuff. The objective of this work was to obtain extruded TPCS/PBAT films containing curcumin and evaluate it as an active antimicrobial and antioxidant packaging to protect chia oil from oxidative degradation. Morphology, thermal, mechanical, antimicrobial, and antioxidant evaluation of the films were conducted to determine whether the presence of curcumin affected the fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…It could be also said that they further comply with the bio-based and biodegradable concept design of sustainable materials and allow usage of recycled cellulose or other bio-polymers for circular economy [ 23 ]. Several studies have demonstrated effectiveness of combining bio-based polyesters with bio-based fillers like poly(butylene adipate-co-terephthalate) (PBAT) with thermoplastic starch for active packaging [ 24 ], PBAT/PLA blends with Babassu for mulch films [ 25 ], chitosan blends with various bio-polyesters like PBS, PLA and others demonstrated antimicrobial activity useful for food preservation and packaging [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…It could be also said that they further comply with the bio-based and biodegradable concept design of sustainable materials and allow usage of recycled cellulose or other bio-polymers for circular economy [ 23 ]. Several studies have demonstrated effectiveness of combining bio-based polyesters with bio-based fillers like poly(butylene adipate-co-terephthalate) (PBAT) with thermoplastic starch for active packaging [ 24 ], PBAT/PLA blends with Babassu for mulch films [ 25 ], chitosan blends with various bio-polyesters like PBS, PLA and others demonstrated antimicrobial activity useful for food preservation and packaging [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of functional or reinforcing fillers such as SiO 2 , graphene oxide, MgO, AgNP, ZnONP, clay, curcumin, grape seed extract, etc. have been utilized enhance the physical and functional properties of PBAT films [ 9 , 15 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. In this sense, the use of natural bioactive compounds to improve PBAT film properties is an attractive field of research.…”
Section: Introductionmentioning
confidence: 99%
“…for biomedical and food packaging applications [ 21 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Recently, De Compos et al reported the preparation of curcumin-reinforced PBAT and thermoplastic cassava starch-based extruded composite films [ 21 ]. In addition, PBAT-based electrospun nanofiber has been developed by reinforcing curcumin and 5-fluorouracil [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, when the material is conditioned to a lower relative humidity, there is a decrease in the molecular mobility of the polymeric chains, resulting in a more rigid structure, which can explain the above mentioned results. Even though there was a reduction in the elongation of the films, their ductility is still considered higher in comparison to other films made with thermoplastic starch (TPS)/curcumina/PBAT (de Campos et al., 2019), TPS/pinhão extract/PBAT (Silva et al., 2019), and TPS/PBAT/PLA (Ren et al., 2009).…”
Section: Resultsmentioning
confidence: 89%
“…starch-films (de Campos et al, 2019). The DTG curves showed an initial peak at around 95 and 100°C for control and films with extracts, respectively.…”
Section: Structural Propertiesmentioning
confidence: 95%